If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -6 + y + 53 = 8y + 50 + -5y Reorder the terms: -6 + 53 + 5y + y = 8y + 50 + -5y Combine like terms: -6 + 53 = 47 47 + 5y + y = 8y + 50 + -5y Combine like terms: 5y + y = 6y 47 + 6y = 8y + 50 + -5y Reorder the terms: 47 + 6y = 50 + 8y + -5y Combine like terms: 8y + -5y = 3y 47 + 6y = 50 + 3y Solving 47 + 6y = 50 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 47 + 6y + -3y = 50 + 3y + -3y Combine like terms: 6y + -3y = 3y 47 + 3y = 50 + 3y + -3y Combine like terms: 3y + -3y = 0 47 + 3y = 50 + 0 47 + 3y = 50 Add '-47' to each side of the equation. 47 + -47 + 3y = 50 + -47 Combine like terms: 47 + -47 = 0 0 + 3y = 50 + -47 3y = 50 + -47 Combine like terms: 50 + -47 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 13t-2=3t+38 | | 11f=5f+36 | | 6(4x-8)=32 | | -8=2c-3c | | xy=120 | | 6-3(6-6x)=0 | | 3.2x+6.5=9.2+11x | | v^2-6v=20+2v | | (3+6)+4=3+(6+4) | | 1(x-4)=-5 | | 2(x+5.75)=15.275 | | 69.8x+42=65 | | 12/k=24k | | 120x+10=150x+4 | | 4x(2)-6x= | | 69.8+42=65 | | 2(x+3)+1=15 | | 56.80x+25.50=78x+100 | | 8x-15y=34 | | A=150*sqrt(3) | | 2(x+1)-5x=2x-8 | | F(x)=x/5-2x | | (2x-3y)(3x+6y)=0 | | 2x-5/6=6 | | (x-y)(x+2y)=0 | | x=2x^2+8x-16 | | (5-1)-2=5-(1-2) | | s-0.2=48 | | 6x+9=9-(3x-5) | | 6xy*5xy+5x= | | f(-3)=9-4 | | t^2+11+24=0 |